Multi-Tooth Contact Analysis and Tooth Profile Modification Optimization for Cycloid Drives in Industrial Robots - Haidong He; Xuan Li; Ting Zhang (Tehnički Vjesnik, 2023)
Cycloid drives are widely used in industrial robots where high load carrying capacity, accurate positioning precision and smooth motion are required strictly. The meshing clearance obtained by tooth profile modifications of cycloid gears is thought to have significant effects on performances of cycloid drives. In this study, this issue is clarified by developing a quasi-static load distribution model with considering four types of tooth profile modifications. Firstly, the unloaded tooth contact analysis is introduced to determine the meshing information, and the nonlinear Hertzian contact mechanics is applied to develop force-displacement relationships, Then, the loads distributed on gears, contact stress, loaded transmission error and gear ratio are calculated by enforcing the deformation compatibility, and force and moment equilibrium conditions. The predicted contact stress and deformation are compared with those by the finite element method, which shows a good agreement. With this, a tooth profile modification optimization method is proposed to obtain the optimal tooth profile modification at given radial clearances by using the two-dimensional parameter map. This study provides a useful tool to predict the multi-tooth contact conditions and to determine the most suitable tooth profile modification during the design process.